2003
DOI: 10.1046/j.1540-8167.2003.02381.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine and Atrial Fibrillation:

Abstract: Serotonin and Atrial Fibrillation. 5‐Hydroxytryptamine, a recent addition to the list of hormonal triggers for atrial fibrillation (AF), may play a pivotal role in the induction of AF related not only to cardiac surgery but also to acute coronary syndromes, valvular heart disease, cardiomyopathies, alcoholism, aging, and conducting tissue disease. This review examines the supporting laboratory and clinical evidence and provides a comprehensive insight into the basic underlying mechanisms involved. It also delv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Even if this proarrhythmic effect of fluoxetine is usually explained by hERG (Kv11.1, a K ϩ channel; for a review, see Ref. 54) and/or L-type Ca 2ϩ current inhibition (42), fluoxetine treatment might increase cardiac levels of 5-HT that can cause cardiac arrhythmias in humans, as mentioned above (58). Our findings might explain, at least in part, these clinical observations.…”
Section: Discussionmentioning
confidence: 53%
“…Even if this proarrhythmic effect of fluoxetine is usually explained by hERG (Kv11.1, a K ϩ channel; for a review, see Ref. 54) and/or L-type Ca 2ϩ current inhibition (42), fluoxetine treatment might increase cardiac levels of 5-HT that can cause cardiac arrhythmias in humans, as mentioned above (58). Our findings might explain, at least in part, these clinical observations.…”
Section: Discussionmentioning
confidence: 53%
“…Serotonin, 5-hydroxytryptamine, is a hormonal trigger for AF [ 45 , 46 ]. By a KEGG analysis, we found that pathways are related to the role of WXKL in AF including the regulation of serotonergic synapses and tryptophan metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…5-HT elevates cAMP content and regulates the concentration of Ca 2+ through 5-HT 4 receptors in human atrial cardiomyocytes [6]. 5-HT 4 receptors were detected in human sinoatrial node and atrial cardiomyocytes; activation of these receptors causes a positive inotropic, chronotropic, lusitropic effects, tachicardia and atrial fibrillation [10,11,15].Hence, the serotoninergic system is involved in the functioning of the cardiovascular system and in the pathogenetic mechanisms of its diseases. However, the role of 5-HT in the regulation of cardiac inotropic function during human postnatal ontogenesis in various congenital heart diseases remains poorly studied.…”
mentioning
confidence: 99%
“…5-HT elevates cAMP content and regulates the concentration of Ca 2+ through 5-HT 4 receptors in human atrial cardiomyocytes [6]. 5-HT 4 receptors were detected in human sinoatrial node and atrial cardiomyocytes; activation of these receptors causes a positive inotropic, chronotropic, lusitropic effects, tachicardia and atrial fibrillation [10,11,15].…”
mentioning
confidence: 99%